STRATEGI RRC DALAM DINAMIKA KONFLIK DI LAUT CHINA SELATAN - Ade Priangani; Jeremy Aldi Rezki Hattu (Jurnal Academia Praja, 2020)
South China Sea (SCS) dispute is a matter of seizure or claim of a territory by some countries is indeed a complicated problem. Conflicts involving China with some members of ASEAN have heated up. To improve relations with ASEAN, China through persuasive attitudes and actions. Due to liberalization strategy of China's political economy over SCS especially to ASEAN. The success of ASEAN over the last 50 years has made ASEAN a market share by the major powers that gave birth to a "rivalry". This research uses descriptive method and historical method, where the research is focused on the plan and action of liberalization of China's political economy to face the rivality of the major countries correlation with the dynamics of SCS conflict. The results of this research are: ASEAN succeeded in maintaining peace of political security stability but difference of opinion related issue of sensitive SCS dispute become challenge entering the next 50 years. SCS is actually becoming OBOR's maritime silk line to Southeast Asia. Facing the rivalry of the big countries, China uses its economic card as a control over ASEAN. AIIB as China's bargaining opportunity to ASEAN. So China can easily get rid of western influence and win ASEAN diplomatically.